Predicting group of metabolites available in partially purified tomato leaves extract showing anticancer activity by high performance liquid chromatography (HPLC) and Fourier transform infrared (FTIR) - Wan Chik, Wan Dalila; Amid, Azura; Jamal, Parveen (Academic Journals, 2011)
Previously, tomato leaves were proved to be one of the potential anticancer agents. High performanceliquid chromatography (HPLC) and Fourier transform infrared (FTIR) spectroscopic instrumentation were used to predict the presence of group of metabolites and to ascertain the possibility of certain absorption bands, in which most of the peaks in partially purified tomato (Solanum lycopersicon)leaves methanol extract are attributed to the specific functional groups. The extraction was carried outin a shake flask with 82% methanol, 1:10 (w/v) sample to solvent ratio, agitated at 22°C with 110 rpm within 24 h. Later, the extract was partially purified by column chromatography. HPLC was used to quantify the number of unknown component presents in the fraction. Then, a FT-IR Bruker Tensor 27 System was used during FTIR data acquisition. The collection of FTIR spectra was carried out at 16 scans with resolution of 4 cm -1 using strong apodization in the frequency regions of 4,000 to 650 cm-1.The results support the premise that HPLC and FTIR spectroscopy are efficient and accurate methods for determining major and minor components presents in the extract.